Factors affecting adoption, implementation fidelity, and sustainability of the Redesigned Community Health Fund in Tanzania: a mixed methods protocol for process evaluation in the Dodoma region - Kalolo, Albino; Radermacher, Ralf; Störmer, Manfred; Meshack, Menoris; De Allegri, Manuela (Global health action, 2015)
BackgroundDespite the implementation of various initiatives to address low enrollment in voluntary micro health insurance (MHI) schemes in sub-Saharan Africa, the problem of low enrollment remains unresolved. The lack of process evaluations of such interventions makes it difficult to ascertain whether their poor results are because of design failures or implementation weaknesses.ObjectiveIn this paper, we describe a process evaluation protocol aimed at opening the ‘black box’ to evaluate the implementation processes of the Redesigned Community Health Fund (CHF) program in the Dodoma region of Tanzania.DesignThe study employs a cross-sectional mixed methods design and is being carried out 3 years after the launch of the Redesigned CHF program. The study is grounded in a conceptual framework which rests on the Diffusion of Innovation Theory and the Implementation Fidelity Framework. The study utilizes a mixture of quantitative and qualitative data collection tools (questionnaires, focus group discussions, in-depth interviews, and document review), and aligns the evaluation to the Theory of Intervention developed by our team. Quantitative data will be used to measure program adoption, implementation fidelity, and their moderating factors. Qualitative data will be used to explore the responses of stakeholders to the intervention, contextual factors, and moderators of adoption, implementation fidelity, and sustainability.DiscussionThis protocol describes a systematic process evaluation in relation to the implementation of a reformed MHI. We trust that the theoretical approaches and methodologies described in our protocol may be useful to inform the design of future process evaluations focused on the assessment of complex interventions, such as MHI schemes.